Deregulation and the banking crisis in Nigeria : a comparative study - Stein, Howard; Ajakaiye, David Olusanya Ishola; Lewis, Peter (New York : Palgrave, 2002)
The book concentrates on the dangers of deregulation in Nigeria with clear implications for the rest of Africa.
Includes bibliographical references and index.
rua 02/03/15; 21/08/15
Loans
Keywords: Banks and banking; Banking crisis